2018
DOI: 10.4103/ijcm.ijcm_382_16
|View full text |Cite
|
Sign up to set email alerts
|

Dietary diversity and stunting among infants and young children: A cross-sectional study in Aligarh

Abstract: Context:Child undernutrition is a public health problem in a developing country like India. Dietary diversity is an important immediate determinant of undernutrition.Aims:The aim of this study is to find the prevalence of stunting among infants and young children aged 6–23 months and its association with dietary diversity.Settings and Design:This study was community-based cross-sectional study. It was carried out in the registered families of the Urban Health Training Centre and Rural Health Training Centre, D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
2
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 11 publications
0
38
2
5
Order By: Relevance
“…Additionally, a national level study conducted in India also indicated that age-appropriate infant and young child feeding practices were associated with child undernutrition [18]. However, while studies from India have reported a high prevalence of delayed introduction of complementary foods [19], as well as a high proportion of stunting among children younger than five years [20,21], there has been no nationally representative studies that investigated the association between delayed introduction of solid, semi-solid or soft foods and associated factors with stunting in India, nor has there been a documented prevalence of stunting by severity. Nationally representative studies in this context are needed as they provide complete information, as well as highlight the characteristics of childhood stunting to match the country's policy directives and interest [22].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a national level study conducted in India also indicated that age-appropriate infant and young child feeding practices were associated with child undernutrition [18]. However, while studies from India have reported a high prevalence of delayed introduction of complementary foods [19], as well as a high proportion of stunting among children younger than five years [20,21], there has been no nationally representative studies that investigated the association between delayed introduction of solid, semi-solid or soft foods and associated factors with stunting in India, nor has there been a documented prevalence of stunting by severity. Nationally representative studies in this context are needed as they provide complete information, as well as highlight the characteristics of childhood stunting to match the country's policy directives and interest [22].…”
Section: Introductionmentioning
confidence: 99%
“…Selain pemberian ASI eksklusif, faktor lain yang juga menyebabkan stunting pada anak adalah ketidaksesuaian keragaman makanan dengan standar. Pemberian makan dengan skor keragaman makanan yang rendah menjadi salah satu faktor risiko kejadian stunting pada anak usia 0˗23 bulan (3,7,8,13,17,24). Sebuah studi membuktikan bahwa anak usia 6˗23 bulan yang mengonsumsi makanan tanpa memperhatikan keragaman makanan memiliki peluang lebih tinggi untuk mengalami stunting dibandingkan anak yang mengonsumsi makanan dengan keragaman ≥5 jenis makanan.…”
Section: Hubungan Stunting Dengan Keragaman Makananunclassified
“…This is a secondary data analysis from data of the Tanzania We used the Kids file (KR file) and Mother file (MR file) from the TDHS data obtained from an online data repository to get information about nutrition status and dietary diversity of children [20]. From 10,233 children of 0-59 month old assessed in the survey, we selected 2,960 younger children aged between 6-23 months living with their mothers.…”
Section: Data Sourcementioning
confidence: 99%
“…Dietary diversity, as a marker of micronutrient adequacy, may increase nutrient density of the complementary foods [15], which promote optimal child growth and development. Receiving an inadequately diversified diet may lead to undernutrition [16], and predispose children to opportunistic infections and severe illnesses Although the association between dietary diversity and the nutritional status of children has already been studied in various countries [16][17][18][19][20][21], studies that use large-scale data are scarce, particularly in Tanzania. In addition, many previous studies in Tanzania have largely focused on other aspects of child nutrition, like micronutrient content[9], complementary feeding practices [9, [22][23][24][25] and their determinants [26,27].…”
Section: Introductionmentioning
confidence: 99%